Radiosurgery for malignant melanoma brain polymetastasis. (31st January 2018) - Meade, Sara; Fong, Charles; Heyes, Geoff; Simmons, Rosemary; Stange, Ruth; Jackson, Timothy; Benghiat, Helen; Cruickshank, Garth; Steven, Neil; Sanghera, Paul; Hartley, Andrew
Abstract: PURPOSE: To compare the outcomes following Cyberknife radiosurgery (SRS) to patients with malignant melanoma with solitary metastasis (SM), oligometastasis (2–4 metastases (OM)) and polymetastasis (>4 metastasis (PM)) within a departmental philosophy of whole brain radiotherapy avoidance for melanoma brain metastases. METHODS: NHS England selection criteria were used. All target volumes were approved by a consultant neuro-radiologist and no planning target volume was used. Thirty-nine patients (SM=18, OM=14, PM=7) were treated June 2013-June 2016. In total 130 individual metastases were treated of which 15 were metachronous following initial SRS. Seven lesions were treated with 3 fractions (24-30Gy), 123 lesions received a single fraction (15-24Gy). The endpoints for this study were lesional control (LC), distant brain control (DBC) and overall survival (OS). RESULTS: For all lesions at 6 months: LC 88%, DBC 72%, OS 77% and at 12 months LC 74%, DBC 50%, OS 50%. DBC at 6months: SM 92%, OM 47%, PM 80% and at 12 months SM 71%, OM 23%, PM 45%. OS at 6 months: SM 86%, OM 67%, PM 85% and at 12 months SM 79%, OM 28%, PM 57%. CONCLUSIONS: Whilst outcomes for SM are as expected, treatment of PM appears feasible and there may be a self selecting subgroup of patients with small volume PM who benefit from SRS in the biological/immune therapy era. The apparent lower rate of DBC and OS with OM and the effect of both lesional volume and biological/immune therapy history will be discussed.